Abattoir waste use in livestock diets: Uganda’s current situation (International Journal of Agricultural Research, Innovation and Technology, 2020)
In this study, we investigated the various ways slaughter wastes are utilized, problems encountered in order to give insights in future prospects of abattoir wastes as livestock feeds. A total of 100 abattoir workers were interviewed through semi-structured questionnaires covering Kampala, Wakiso and Mukono districts in Uganda. Results revealed that majority of abattoir work force were middle-aged adults between 30-45 years contributing 37% of total workers. There was a significant association between abattoir workers responses in relation to the proportion of livestock slaughtered (Chi square 147.55; df =2; p